Pressure gradient and geometrical variation of the abrasive blocks during the polishing process of ceramic tiles with line contact - Amiril Sahab, Abdul Sani (2014)
A series of experimental investigation has been carried out to develop and describe the distribution of pressure gradient underneath and across the topological surface of laboratory grinding tools. The surface pressure plays a key role during polishing process of ceramic tiles in gloss gaining and development of surface roughness. Analogous to the surface topography changes of the grinding tools and ceramic tiles, the wear of the work tools and work pieces are proportional to the grinding work that was performed between the surfaces during the polishing process. The present work intends to evaluate the influence of the gradual distribution of surface pressure in polishing ceramic tiles with line contact. For this purpose, two grinding tools were assembled together as a polishing head and installed on a CNC tribometer machine with a deflection angle of 2.2° from the base coordinate system of the machine. In this thesis, the theory of pressure distributed gradually underneath and across the polishing tools was successfully defined by implementing a new polishing tool composed of rotating shaft with pivot joint, helical springs and two abrasive blocks attached on it. These findings enhance the understanding of pressure distribution from previous study of polishing with flat contact using single abrasive block. With these comparisons the process outcome in terms of gloss level and fine surface finish could be further optimised. The effect of the material removal and gloss development due to polishing tools configuration with preferred process parameters were found to be minimised or maximised according to the kinematics chosen. Differences were clearly illustrated at the end of the work.